Analysis of the Antennal Transcriptome and Identification of Tissue-specific Expression of Olfactory-related Genes in Micromelalopha troglodyta (Lepidoptera: Notodontidae). Issue 5 (27th September 2022) - Zhang, Yu; Feng, Kai; Mei, Ruolan; Li, Wei; Tang, Fang
Abstract: Micromelalopha troglodyta (Graeser) has been one of the most serious pests on poplars in China. We used Illumina HiSeq 2000 sequencing to construct an antennal transcriptome and identify olfactory-related genes. In total, 142 transcripts were identified, including 74 odorant receptors (ORs), 32 odorant-binding proteins (OBPs), 13 chemosensory proteins (CSPs), 20 ionotropic receptors (IRs), and 3 sensory neuron membrane proteins (SNMPs). The genetic relationships were obtained by the phylogenetic tree, and the tissue-specific expression of important olfactory-related genes was determined by quantitative real-time PCR (qRT–PCR). The results showed that most of these genes are abundantly expressed in the antennae and head. In most insects, olfaction plays a key role in foraging, host localization, and searching for mates. Our research lays the foundation for future research on the molecular mechanism of the olfactory system in M. troglodyta . In addition, this study provides a theoretical basis for exploring the relationship between M. troglodyta and their host plants, and for the biological control of M. troglodyta using olfactory receptor as targets.